Nitrogen-sulphur Co-doped graphenes modified electrospun lignin/polyacrylonitrile-based carbon nanofiber as high performance supercapacitor - Dai, Zhong; Ren, Peng-Gang; Jin, Yan-Ling; Zhang, Hua; Ren, Fang; Zhang, Qian (Journal of power sources, 2019)
Persuing both high energy and power density in one supercapacitor at low cost is very challenging to date. Here, we report the fabrication of nitorgen and Sulphur co-doped graphene (GN) modified lignin/polyacrylonitrile (PAN)-based carbon nanofiber (ACNFs) from mainly the biomass of lignin following a process of electrospinning, carbonization and activation. GN is used as nitrogen/sulphur immobilization agent to successfully capture HCN, NH3 and SO2 released from lignin and PAN during carbonization, and thus the content of heteroatoms of N and S in ACNFs is increased. The resulting ACNF with 0.30 wt% GN content possesses the maximum specific surface area of 2439 m2 g−1. It shows a typical three-dimensional porous network structures with the highest heteroatom doping content and high degree of crystallinity. The assembled supercapacitor exhibits superior electrochemical performance with ultra-high specific capacitance of 267.32 F g−1, low equivalent series resistance of 5.67 Ω, and outstanding cycling stability of 96.7% capacitance retention after 5000 cycles of charge/discharge in a two-electrode system with 6 mol L−1 KOH as electrolyte. Most importantly, the assembled symmetric supercapacitor shows that ACNFs doping with GNs increases the energy density from 4.12 to 9.28 Wh kg−1 and at the same time with barely reduced power density. •Using GNs as an adsorbent to capture HCN, NH3, SO2 released in carbonization.•Proposing the water wetting behaviour to evaluation the supercapacitor performance.•Elucidated the mechanism between heteroatom doping and electrochemical properties.